Mechanics of flight - Kermode, A. C.; Philpott, D.r.; Barnard, R. H. ([S.l.] : Pearson ed, 2012)
Mechanics of Flight is an ideal introduction to the basic principles of flight for students embarking on courses in aerospace engineering, student pilots, apprentices in the industry and anyone who is simply interested in aircraft and space flight. Written in a straightforward and jargon-free style, this popular classic text makes the fascinating topic of aircraft flight engaging and easy to understand. Starting with an overview of the relevant aspects of mechanics, the book goes on to cover topics such as air and airflow, aerofoils, thrust, level flight, gliding, landing, performance, manoeuvres, stability and control. Important aspects of these topics are illustrated by a description of a trial flight in a light aircraft. The book also deals with flight at transonic and supersonic speeds, and finally orbital and space flight.